TNFAIP6 promotes invasion and metastasis of gastric cancer and indicates poor prognosis of patients. (February 2021) - Zhang, Xiangwen; Xue, Jiaming; Yang, Huiliang; Zhou, Tingting; Zu, Guo
Highlights: TNFAIP6 overexpression increased with depth of tumor invasion, lymph node metastasis and TNM stage of gastric cancer. The patients with high TNFAIP6 expression exhibited poor prognosis of gastric cancer patients. Knockdown of TNFAIP6 could inhibit the proliferation, invasion and metastasis of gastric cancer cells. Abstract: TNFα-stimulated gene-6 (TNFAIP6) plays an important role in the prognosis of many tumors. Our objective was to investigate the clinical and prognostic value of TNFAIP6 expression in gastric cancer (GC) patients. Here, we investigated the expression of TNFAIP6 in GC tissues using western blotting and immunohistochemistry and the association between TNFAIP6 expression and the prognosis and clinicopathological parameters of GC patients. Our results revealed that the expression of TNFAIP6 was higher in GC tissue than in normal gastric tissue, and the levels were positively correlated with the depth of tumor invasion (P = 0.010), tumors with lymph node metastasis (P = 0.000) and TNM stage (P = 0.003) of GC patients. Moreover, the results revealed that patients with high TNFAIP6 expression exhibited poorer overall survival than those with low TNFAIP6 expression (P = 0.037). Additionally, knockdown of TNFAIP6 inhibited the proliferation, invasion and metastasis of GC cells in vitro. High TNFAIP6 expression was associated with the depth of tumor invasion, lymph node metastasis, TNM stage and poor prognosis of GC patients, suggesting that TNFAIP6 may serve as a novel indicator of the prognosis and as a treatment target of GC.